Reticulo-ruminal milk accumulation (ruminal drinking) in five pre-ruminant white-tailed deer (Odocoileus virginianus) in Texas - Adetunji, Shakirat A.; Gomez, Gabriel; Concha-Bermejillo, Andres De la; Oliveira, Fabiano; Arenas-Gamboa, Angela M. (Brazilian Journal of Veterinary Pathology, 2016)
Ruminal drinking is a condition that has been extensively reported in pre-ruminant calves, and is characterized by an insufficient esophageal groove reflex that causes ingested milk to spill into the reticulum and/or rumen instead of entering the abomasum directly. In calves, milk that spills into the rumen undergoes rapid microbial fermentation, producing lactic acid and other volatile fatty acids, and lowering the ruminal pH. This reduced ruminal pH predisposes the animals to ulceration and necrosis of the rumen mucosa, as well as maldigestion and recurrent tympany. We investigated five cases of ulcerative rumenitis in white-tailed deer (WTD: Odocoileus virginianus) fawns from 2009 to 2014. Four of these fawns were females with ages ranging from 2 to 30 days. Clinical findings in the fawns included poor body condition, severe diarrhea, and sudden death. Gross changes consistently observed included large amount of milk and milk curds in the rumen, reticulum and occasionally omasum, white-colored and bloody diarrhea, severe muscle wasting with extensive loss of visceral fat. On microscopic examination, the most consistent finding among three of the animals was multifocal necroulcerative rumenitis admixed with basophilic globular material (milk), while the other two animals had unremarkable histopathologic findings. Aerobic and anaerobic bacterial cultures of samples collected revealed mixed bacterial growth suggestive of secondary opportunistic invasion. Molecular diagnostics ruled out the possibility of Bluetongue and Epizootic Hemorrhagic viral infections. This report describes for the first time, clinical, gross, and microscopic changes associated with reticulo-ruminal milk accumulation in WTD fawns across farms in Texas, and complements those of earlier studies in calves.